2023
DOI: 10.1177/23259671221142315
|View full text |Cite
|
Sign up to set email alerts
|

Failure Rates After Anterior Cruciate Ligament Repair With Suture Tape Augmentation in an Active-Duty Military Population

Abstract: Background: Anterior cruciate ligament (ACL) repair had previously been considered the standard of care for a ruptured ACL; however, ACL reconstruction has became the standard of care because of poor midterm outcomes after ACL repair. Recently, studies have suggested that the treatment paradigm should shift back to ACL repair. Purpose/Hypothesis: The purpose of this study was to evaluate the outcomes of ACL repair augmented with suture tape in a high-demand military population. We hypothesized that for proxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Cruz et al 4 reported the highest revision rate after ACL repair with SA in a high-demand military cohort of 46 patients. At the 2-year follow-up, they found a revision rate of 26.1%.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Cruz et al 4 reported the highest revision rate after ACL repair with SA in a high-demand military cohort of 46 patients. At the 2-year follow-up, they found a revision rate of 26.1%.…”
Section: Discussionmentioning
confidence: 97%
“…Concomitant injuries were initially seen as a contraindication to performing an ACL repair with SA 6 ; however, studies have included patients with concomitant ligamentous, meniscal, and chondral lesions with an ACL injury but have not assessed them as potential risk factors for revision surgery. 7,12 In their analysis, Cruz et al 4 were not able to identify meniscal or The Orthopaedic Journal of Sports Medicine Revision Surgery ACL Repair 5 chondral concomitant injuries as a risk for revision surgery after ACL repair with SA. Cruz et al 4 reported a significantly higher mean interval between injury and surgery in the failure group (164 6 59 days compared with 107 6 98 days in the nonfailure group).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A sampling of other recent studies of ACL repair, reconstruction, or revision reconstruction in AJSM and OJSM reveals a variety of definitions of failure, including history of giving way, 16,19,21,22 laxity on instrumented physical examination, 2,6,15,16,19,22 MRI evidence of disruption, 2,3,6,10,15,21,22 graft rupture by history, 11 symptomatic instability, 10 and rerupture or symptomatic instability requiring revision surgery. 3,6,10,11,16,21 Studies often used multiple criteria, and symptoms suggestive of possible failure frequently led to further documentation by instrumented examination and MRI. A letter to the editor by DiFelice and colleagues 5 suggested another nuance in the definition of failure in the case of ACL repair.…”
mentioning
confidence: 99%